A responsabilização do Estado e a destinação dos recursos do Fundo de Defesa de Direitos Difusos nas ações de reparação dos danos ambientais - Zanquim Junior, José Wamberto (2021)
Anthropogenic actions impact the environment and restoration of damages is essential and inescapable. The in natura repair of environmental damage must always be sought after and, only as a last resource should it be reduced to monetary values. The Term of Commitment to Environmental Recovery aims at a consensual way to lay out the measures to repair the environment, forming an extrajudicial executive title. This reparation finds legal ground in the constitutional and infra-constitutional legislation, assigning solidarity to all offenders, direct or indirect. The Public Power will be jointly liable for damage to the environment. However, when held responsible for omission, will be in a secondary position of accountability. Portuguese international law and United States law provide that, for environmental damage in situations of irreparability, regardless of cause being the non-identification of offenders or failure to adopt sufficient measures for the return of the status quo, the Public Authorities may carry out reparative actions on the degraded environment, keeping the right of return. The situation favors the right to a balanced environment and maintenance of environmental quality over the use of public resources for the reparation. Therefore, the present thesis, in a complementary setup, proposes an amendment to the regulatory decree for the use of pecuniary resources obtained by the Fund for the Defense of Diffuse and Collective Rights regarding the expression “priority” provided for in the Sole Paragraphof art. 7 of Decree 1.306/1994 and its replacement by the expression “exclusively”. Thus, in the field of propositions for the effectiveness of repairs in natura, this thesis serves to suggest the adoption in domestic law, in accordance with international law, of the accountability of Public Power on adoption of environmental reparative actions, as well as suggest amending the infra-constitutional legislation, especially Decree n. 1306/1994 which regulates the use of resources from the FDD. For the scope of research, factual data was obtained from the Environmental Company of the State of São Paulo - CETESB, regarding environmental administrative procedures in which TCRAs in the city of São Carlos - SP. The data is from years 2012 through 2016 and aims to verify effectiveness of the agreements on the degraded environment restoration. It was found that the TCRA was effective in most cases, however, there were degraded areas left without any repair action, justifying the proposal offered by this research. Likewise, the theoretical basis possible through bibliographic review allowed laying down the foundations and all the arguments surrounding the need to promote changes in domestic law for the feasibility of environmental repair in natura in accordance with international legislation. To this end, this research found its guidelines in books, periodicals, scientific articles, theses and dissertations, environmental diagnosis reports and in environmental administrative procedures, making use of the synergistic combination between theoretical elements and factual data extracted from the experienced reality. It can be concluded the environmental agreements are effective and there is need for new instruments for effective environmental repair.